1986
DOI: 10.29203/ka.1986.242
|View full text |Cite
|
Sign up to set email alerts
|

Polypores in the parks and forests of the City of Helsinki

Abstract: The polypores of the Helsinki municipal area in South Finland were studied with regard to their microdistributions, host relationships, abundances and economic importance. Altogether 120 species are reported. Five site types were defined, ranging from urban to rural environments: parks proper, tree rows, park forests, forests proper and idle land areas. Distinct differences were found in the species composi ti ons of urban environments (parks proper and tree rows), as compared with more natural wooded areas (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…For a discussion on this nomenclatural issue see Donk (1960), Larsen and Lombard (1986) and Walker (1996), who support the use of Postia, and Ryvarden (1991), who supports the use of Oligoporus. The exception between these positions is the one adopted by Erkkilä and Niemelä (1986) and Renvall (1992), who proposed the use of both names: Postia for taxa with thin-walled basidiospores and Oligoporus for taxa having broadly ellipsoid to short cylindrical basidiospores with thickened, cyanophilous walls, and which have a tendency to form chlamydospores in nature and/or culture.…”
Section: Introductionmentioning
confidence: 99%
“…For a discussion on this nomenclatural issue see Donk (1960), Larsen and Lombard (1986) and Walker (1996), who support the use of Postia, and Ryvarden (1991), who supports the use of Oligoporus. The exception between these positions is the one adopted by Erkkilä and Niemelä (1986) and Renvall (1992), who proposed the use of both names: Postia for taxa with thin-walled basidiospores and Oligoporus for taxa having broadly ellipsoid to short cylindrical basidiospores with thickened, cyanophilous walls, and which have a tendency to form chlamydospores in nature and/or culture.…”
Section: Introductionmentioning
confidence: 99%
“…Parm. In Fennoscandia, Betula is cited as the main host of P. igniarius (Eriksson 1958;Niemela 1975;Niemela & Kotiranta 1982;Erkkila & Niemela 1986;Renvall et al 1991); besides , the taxon is found on Salix and numerous other trees . As well, in the eastern part of Europe and the territory of the former USSR Betula is reported as common host (Bondartsev 1953 ;Domanski et al 1973).…”
mentioning
confidence: 99%
“…squamasus remain relatively safe even if the fungus has decayed them for decades. The "park ecotype" is common chiefly in old downtown parks of Helsinki (Erkkila & Niemela 1986) and Turku, and its distribution does not show any dependence on lakes, rivers or other waters. Erkkila and Niemela (1986) suggested that this "park ecotype" might be a neophyte in Finland, originating from Central Europe and being established only in parks in the north.…”
Section: (See Overleaf For Host List)mentioning
confidence: 99%
“…The "park ecotype" is common chiefly in old downtown parks of Helsinki (Erkkila & Niemela 1986) and Turku, and its distribution does not show any dependence on lakes, rivers or other waters. Erkkila and Niemela (1986) suggested that this "park ecotype" might be a neophyte in Finland, originating from Central Europe and being established only in parks in the north. Indeed, host trees are often exotic cultivars and, for instance, large Ulmus trees in nature seem to be free of this parasite (P. Uotila pers.…”
Section: (See Overleaf For Host List)mentioning
confidence: 99%
See 1 more Smart Citation